La telenovela y la representación de las mujeres negras: un estudio a partir de la categoría analítica imágenes de control - Effgen Santos, Matheus; Santos Alves, Gabriela (Pontificia Universidad Católica del Perú, 2023)
In Brazil, the telenovela has established itself as one of the most important products of television. Thus, it addresses the differences between social groups and disputes between them. The visibility for these groups that is built from this dynamic becomes a chance to promote their representation, when they see themselves as part of the nation. This study aims to understand the representation of Black women in the scenario of contemporary Brazilian telenovelas, focusing on Amor de Mãe (2019-2021). The research consisted of analyzing the protagonists of the first part of this narrative, Camila (Jéssica Ellen) and Vitória (Taís Araújo), based on the analytical category of controlling images (Collins, 2019), which unravels the logic that tries to justify the oppression experienced by these women. The results show that these images can be identified isolated and/or combined in the construction of these characters. At times, the telenovela plot questions these images; at others, it reinforces them.

En Brasil, la telenovela se ha establecido como uno de los productos más importantes de la televisión. Por lo tanto, aborda las diferencias entre los grupos sociales y las disputas entre ellos. La visibilidad para estos grupos que se construye a partir de esta dinámica se convierte en una oportunidad para promover su representación, cuando se ven a sí mismos como parte de la nación. Este estudio tiene como objetivo comprender la representación de las mujeres negras en el escenario de las telenovelas brasileñas contemporáneas, específicamente, en Amor de Mãe (2019-2021). La investigación consistió en analizar a los protagonistas de la primera parte de esta narrativa, Camila (Jéssica Ellen) y Vitória (Taís Araújo), a partir de la categoría analítica imágenes de control (Collins, 2019), que desentraña la lógica que trata de justificar la opresión experimentada por estas mujeres. Los resultados muestran que estas imágenes pueden ser identificadas aisladas o combinadas en la construcción de estos personajes. A veces, la trama de la telenovela cuestiona estas imágenes; en otras, las refuerza.
The Telenovela and the Representation of Black Women: A Study from the Controlling Images Analytical Category
Keywords: telenovela; representation; black woman; Amor de Mãe; telenovela; representación; mujer negra; Amor de Mãe; https://purl.org/pe-repo/ocde/ford#5.09.01